From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

New insights into gas-driven phase segregation in andesitic enclaves from Mt. Mazama (Crater Lake), USA - Julie Oppenheimer; Katharine V. Cashman; Alison C. Rust; Charles R. Bacon; Amanda Lindoo; Katherine J. Dobson (Bulletin of Volcanology, 2025)
A key process in active magmatic systems is the “recharge” of deep-sourced mafic magma into cooler, more evolved, and crystal-rich shallow reservoirs; recharge may be the cause of, or response to, eruptive activity. Although compositional evidence for recharge has been extensively documented, physical models of recharge are limited, particularly processes that separate exsolving volatiles and melts from rapidly growing crystals. To improve constraints on phase separation behaviors, we re-examine andesitic enclaves in silicic andesite lava flows of Mt. Mazama (Crater Lake), USA, that provided early evidence of gas-driven filter pressing (Bacon, 1986). 2D and 3D imaging shows that enclaves have a sample-spanning crystal framework that is disrupted by melt patches, indicating that initially deformable crystal networks were subject to early phase reorganization. Small enclaves are poorly vesicular and require early gas loss. Large enclaves have porous cores with angular (diktytaxitic) voids that are well-connected in 3D and denser rinds with isolated pores. Large enclave rinds have similar bulk compositions to small enclaves but their less evolved cores require ~ 20% melt removal. In the large enclave, diktytaxitic core textures and gas fingering structures at the core–rind boundary suggest relatively slow late-stage outward gas migration. Both scaling arguments and evidence of outward gas/melt migration require a resistant rind. Rind formation is best explained by differential cooling and demonstrates the importance of thermal gradients for gas-driven filter pressing. A corollary is a limited time scale of recharge, enclave formation, and vesiculation to produce diktytaxitic textures, suggesting that recharge was (near) synchronous with eruption.

Effect of intertidal air exposure and handling husbandries on shell development, meat condition and survival of farmed Pacific oysters (Magallana gigas, Thunberg 1793) - Ernest O. Chuku; Gregory G. Smith; Debashish Mazumder; Steven A. Rust; Andrew J. Trotter (Aquaculture, 2025)

Polymer coated urea does not improve nitrogen use efficiency above urea in ratoon sugarcane crops in the wet subtropics - Terry J. Rose; Josh Rust; Lukas Van Zwieten; Michael T. Rose (Nutrient Cycling in Agroecosystems, 2025)

The effect of interstimulus interval on sustained attention - Bonnie Humphrey; Daniel B. Stouffer; Averill Moser-Rust; William S. Helton; Randolph C. Grace; Ximena J. Nelson (Behavioural Processes, 2024)

The voice of choice: A scoping review of choice-based animal welfare studies - Kelli Rust; Isabella Clegg; Eduardo J. Fernandez (Applied Animal Behaviour Science, 2024)

Magnetotelluric investigations at Andean volcanoes: Partial melt or saline magmatic fluids? - A.P. Jenkins; A.C. Rust; J. Blundy; J. Biggs (Journal of Volcanology and Geothermal Research, 2023)

Implications of fire-induced evapotranspiration shifts for recharge-runoff generation and vegetation conversion in the western United States - Natalie M. Collar; Brian A. Ebel; Samuel Saxe; Ashley J. Rust; Terri S. Hogue (Journal of Hydrology, 2023)

Magma fragmentation: a perspective on emerging topics and future directions - Thomas J. Jones; Katharine V. Cashman; Emma J. Liu; Alison C. Rust; Bettina Scheu (Bulletin of Volcanology, 2022)
The breaking apart of magma into fragments is intimately related to the eruptive style and thus the nature and footprint of volcanic hazards. The size and shape distributions of the fragments, in turn, affect the efficiency of heat transfer within pyroclastic plumes and currents and the settling velocity, and so the residence time, of particles in the atmosphere. Fundamental work relating the glass transition to the fragmentation of magmas remains at the heart of conceptual and numerical models of volcanic eruptions. Current fragmentation criteria, however, do not predict the sizes and shapes of the resulting fragments, or fully account for the multiphase nature of magmas or ways in which magma can break in a fluidal manner or by thermal stress. The pulsatory, non-steady state nature of some eruptions, and related interactions with these fragmentation criteria, also requires further investigation. Here, we briefly review some recent advances in the field of magma fragmentation and provide a perspective on how integrated field, experimental and numerical modelling studies can address key outstanding challenges.

Large silicic magma bodies and very large magnitude explosive eruptions - R. S. J. Sparks; J. D. Blundy; K. V. Cashman; M. Jackson; A. Rust; C. J. N. Wilson (Bulletin of Volcanology, 2022)
Over the last 20 years, new concepts have emerged into understanding the processes that lead to build up to large silicic explosive eruptions based on integration of geophysical, geochemical, petrological, geochronological and dynamical modelling. Silicic melts are generated within magma systems extending throughout the crust by segregation from mushy zones. Segregated melt layers become unstable and can assemble into ephemeral upper crustal magma chambers rapidly prior to eruption. In the next 10 years, we can expect major advances in dynamical models as well as in analytical and geophysical methods, which need to be underpinned in field research.

Sketching sustainable land use in Europe by 2040: a multi-stakeholder participatory approach to elicit cross-sectoral visions - Marta Pérez-Soba; James Paterson; Marc J. Metzger; Marc Gramberger; Joske Houtkamp; Anne Jensen; Dave Murray-Rust; Pieter J. Verkerk (Regional Environmental Change, 2018)

How do Europeans want to live in 2040? Citizen visions and their consequences for European land use - Marc J. Metzger; Dave Murray-Rust; Joske Houtkamp; Anne Jensen; Inge La Riviere; James S. Paterson; Marta Pérez-Soba; Christiane Valluri-Nitsch (Regional Environmental Change, 2018)

Contrasting mechanisms of magma fragmentation during coeval magmatic and hydromagmatic activity: the Hverfjall Fires fissure eruption, Iceland - E. J. Liu; K. V. Cashman; A. C. Rust; A. Höskuldsson (Bulletin of Volcanology, 2017)

MeMoVolc consensual document: a review of cross-disciplinary approaches to characterizing small explosive magmatic eruptions - L. Gurioli; D. Andronico; P. Bachelery; H. Balcone-Boissard; J. Battaglia; G. Boudon; A. Burgisser; M. R. Burton; K. Cashman; S. Cichy; R. Cioni; A. Di Muro; et al. (Bulletin of Volcanology, 2015)

Evolution of crust- and core-dominated lava flows using scaling analysis - Angelo Castruccio; A. C. Rust; R. S. J. Sparks (Bulletin of Volcanology, 2013)

Utilization of Biochar in Sugarcane and Sugar-Industry Management - R. G. Quirk; L. Van Zwieten; S. Kimber; A. Downie; S. Morris; J. Rust (Sugar Tech, 2012)

Generation of the Sotos syndrome deletion in mice - Anna M. Migdalska; Louise van der Weyden; Ozama Ismail; Alistair G. Rust; Mamunur Rashid; Jacqueline K. White; Gabriela Sánchez-Andrade; James R. Lupski; Darren W. Logan; Mark J. Arends; David J. Adams (Mammalian Genome, 2012)

The influence of synoptic airflow on UK daily precipitation extremes. Part II: regional climate model and E-OBS data validation - Douglas Maraun; Timothy J. Osborn; Henning W. Rust (Climate Dynamics, 2012)

Multiphase petrography of volcanic rocks using element maps: a method applied to Mount St. Helens, 1980–2005 - D. D. Muir; J. D. Blundy; A. C. Rust (Bulletin of Volcanology, 2012)

The influence of synoptic airflow on UK daily precipitation extremes. Part I: Observed spatio-temporal relationships - Douglas Maraun; Timothy J. Osborn; Henning W. Rust (Climate Dynamics, 2011)

Effects of biochar from slow pyrolysis of papermill waste on agronomic performance and soil fertility - L. Van Zwieten; S. Kimber; S. Morris; K. Y. Chan; A. Downie; J. Rust; S. Joseph; A. Cowie (Plant and Soil, 2010)

The annual cycle of heavy precipitation across the United Kingdom: a model based on extreme value statistics - D. Maraun; H. W. Rust; T. J. Osborn (International Journal of Climatology, 2009)
The annual cycle of extreme 1‐day precipitation events across the UK is investigated by developing a statistical model and fitting it to data from 689 rain gauges. A generalized extreme‐value distribution (GEV) is fit to the time series of monthly maxima, across all months of the year simultaneously, by approximating the annual cycles of the location and scale parameters by harmonic functions, while keeping the shape parameter constant throughout the year. We average the shape parameter of neighbouring rain gauges to decrease parameter uncertainties, and also interpolate values of all model parameters to give complete coverage of the UK. The model reveals distinct spatial patterns for the estimated parameters. The annual mean of the location and scale parameter is highly correlated with orography. The annual cycle of the location parameter is strong in the northwest UK (peaking in late autumn or winter) and in East Anglia (where it peaks in late summer), and low in the Midlands. The annual cycle of the scale parameter exhibits a similar pattern with strongest amplitudes in East Anglia. The spatial patterns of the annual cycle phase suggest that they are linked to the dominance of frontal precipitation for generating extreme precipitation in the west and convective precipitation in the southeast of the UK. The shape parameter shows a gradient from positive values in the east to negative values in some areas of the west. We also estimate 10‐year and 100‐year return levels at each rain gauge, and interpolated across the UK. Copyright © 2008 Royal Meteorological Society

Postglacial fault movement and palaeoseismicity in western Scotland: A reappraisal of the Kinloch Hourn fault, Kintail - Iain S. Stewart; Callum R. Firth; Derek J. Rust; Philip E.F. Collins; Judith A. Firth (Journal of Seismology, 2001)

Mapping porosity variation in a welded pyroclastic deposit with signal and velocity patterns from ground-penetrating radar surveys - A. C. Rust; J. K. Russell (Bulletin of Volcanology, 2001)

Bioencapsulation of erythromycin using adult brine shrimp, Artemia franciscana (Latreille) - T J. Majack; M B. Rust; K C. Massee; . G. W. Kissil; R W. Hardy; M E. Peterson (Journal of Fish Diseases, 2000)
Live adult brine shrimp, Artemia franciscana (Latreille), were enriched with erythromycin to determine if Artemia could accumulate therapeutic levels for subsequent feeding to young fish. Three trials were conducted to determine the erythromycin incorporation and survival rates of enriched Artemia when fed either liposomes containing erythromycin or various erythromycin suspensions. Erythromycin concentration in Artemia fed a liposome suspension was low (∼ 5 μg mL −1 ) relative to Artemia fed the direct suspension (> 100 μg mL −1 ) over the same time period. When enriched with suspensions up to 1 g erythromycin L −1 sea water for 14 h, Artemia survival was not significantly affected ( P > 0.05) relative to controls. Using a suspension of 1 g L −1 , tissue erythromycin concentrations of 109 ± 16 μg erythromycin mL −1 Artemia homogenate (mean ± SEM) were achieved after 12 h. Concentrations above 170 μg mL −1 were obtained using suspensions of 2–5 g L −1 , but Artemia survival significantly ( P

Caste differences in feeding and trophallaxis in the western drywood termite, Incisitermes minor (Hagen) (Isoptera, Kalotermitidae) - B. J. Cabrera; M. K. Rust (Insectes Sociaux, 1999)

Urinary excretion of acetylcyanamide in rat and human after oral and dermal application of hydrogen cyanamide (H2NCN) - B. Mertschenk; W. Bornemann; J. G. Filser; L. von Meyer; U. Rust; J. -C. Schneider; Ch. Gloxhuber (Archives of Toxicology, 1991)